Youth homicide in the Americas: a subregional analysis, 1989–2006. (1st March 2011) - Cerda, M; Concha-Eastman, A
Abstract : Homicide is one of the leading causes of death for youth aged 10–29 years of age in the America. We reviewed youth mortality data from the America, derived from reliable national civil registration systems, and conducted analyses by subregion, age, sex and time, using semi-parametric group-based modelling to identify clusters of countries that followed similar trends in homicide over time. The age-homicide curve is highest among males: while the homicide rate per 100 000 inhabitants among males ranged from 3.6 at ages 10–14 to 77.9 at 25–29, among women, rates ranged from 1.4 at ages 10–14 to 6.4 at 25–29. Youth homicide rates varied markedly between subregions: the Andean subregion had the highest rates of homicide (3.7–106.5 per 100 000, depending on the age group), and the Latin Caribbean had the lowest rates (0–9.5 per 100 000). Group-based modelling indicated that four to six different types of homicide temporal trends existed in the region, depending on the age group. The most prevalent group of countries (44–57% of the sample) exhibited a stable pattern of low homicide rates, while 5–13% had stable moderate rates of homicide and 2–6% had fluctuating high rates of homicide. Group-based modelling can help us identify the different homicide trajectories that countries follow over time, and evaluate how changing public policies may change regional patterns of homicide and place countries on lower homicide trajectories.